SOCIAL RESPONSIBILITY DISCLOSURE OF ISLAMIC BANKING IN SOUTHEAST ASIA BASED ON ISLAMIC SOCIAL REPORTING INDEX - Ely Windarti Hastuti; Purwo Hadi Santoso; Mutia Asmarani Wibowo; Cahaya Fitriana Dewi Amala (Ekonomi Islam, 2022)
The study aims to analyze how the disclosure of Corporate Social Responsibility (CSR) in Islamic banking in southeast Asia based on the Islamic Social Responsibility Index. This study uses secondary data obtained from the annual report of Islamic banking in Southeast Asia which has been published for the period of 2020. The method used in this study is content analysis of the annual reports of Islamic banking. The results of this study indicate that the disclosure of CSR in Islamic banking in Southeast Asia in general has made quite informative disclosed. The disclosure of CSR has not fully implemented the Islamic Social Reporting Index with AAOIFI standards. This is due to the large number of disclosures of social performance in Islamic banking which refers to the Global Reporting Index.